Revisiting Adam Smith’s Free Market through the Lens of Islamic Economics - Sopian (Islamicate Institute, 2025)
This paper revisits Adam Smith’s free-market theory through the ethical framework of Islamic economics. Drawing from both classical and modern sources, it contrasts Smith’s concept of self-interest and limited state with Islamic doctrines of adl, maslahah, and divine accountability. The study finds that while Smithian capitalism emphasizes efficiency and liberty, it lacks institutionalized moral restraints. Islamic economics complements this gap through mechanisms such as zakāh, hisbah, and waqf, which align market activity with justice and social welfare. The proposed synthesis—the “Islamicized free market”—retains the productive efficiency of Smith’s model while embedding it within a divinely mandated moral order. This integration offers a viable alternative to secular capitalism, promoting balanced growth, equity, and sustainability.